2013
DOI: 10.3389/fpls.2013.00470
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of the Calvin–Benson cycle: something old, something new

Abstract: Reversible redox post-translational modifications such as oxido-reduction of disulfide bonds, S-nitrosylation, and S-glutathionylation, play a prominent role in the regulation of cell metabolism and signaling in all organisms. These modifications are mainly controlled by members of the thioredoxin and glutaredoxin families. Early studies in photosynthetic organisms have identified the Calvin–Benson cycle, the photosynthetic pathway responsible for carbon assimilation, as a redox regulated process. Indeed, 4 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
336
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(368 citation statements)
references
References 255 publications
(375 reference statements)
9
336
0
3
Order By: Relevance
“…It is well known that light reactions of photosynthesis generate abundant reactive oxygen species (Balsera et al, 2014;Schmitt et al, 2014) and may activate the transcription of SMT15 in order to maintain glutathione homeostasis and thereby mitigate cellular damage and stress caused by reactive oxygen species. Equally possible is that glutathione levels are directly coupled to the glutathionylation/deglutathionylation of proteins required for photosynthetic activities as cells grow (Zaffagnini et al, 2012;Michelet et al, 2013).…”
Section: Smt15 Glutathione and Cell Cycle Controlmentioning
confidence: 99%
“…It is well known that light reactions of photosynthesis generate abundant reactive oxygen species (Balsera et al, 2014;Schmitt et al, 2014) and may activate the transcription of SMT15 in order to maintain glutathione homeostasis and thereby mitigate cellular damage and stress caused by reactive oxygen species. Equally possible is that glutathione levels are directly coupled to the glutathionylation/deglutathionylation of proteins required for photosynthetic activities as cells grow (Zaffagnini et al, 2012;Michelet et al, 2013).…”
Section: Smt15 Glutathione and Cell Cycle Controlmentioning
confidence: 99%
“…In higher plants, the plastid-localized TRX family can be classified into five subgroups, including two f-type (TRX f1 and f2), four m-type (TRX m1-m4), one x-type (TRX x), two y-type (TRX y1 and y2), and one z-type (TRX z) TRX isoforms (Michalska et al, 2009;Michelet et al, 2013;Serrato et al, 2013;Balsera et al, 2014). Numerous in vitro and in vivo studies have shown that TRX f and TRX m are required for multiple metabolic processes in chloroplasts, including the Calvin-Benson cycle (Collin et al, 2003;Michelet et al, 2013;Okegawa and Motohashi, 2015;Yoshida et al, 2015), ATP synthesis (Schwarz et al, 1997) and NADPH export (Wolosiuk et al, 1979;Lara et al, 1980), starch metabolism (Fu et al, 1998;Mikkelsen et al, 2005;Seung et al, 2013;Thormählen et al, 2013), fatty acid synthesis (Sasaki et al, 1997), amino acid synthesis (Balmer et al, 2003), and chlorophyll (Chl) synthesis (Ikegami et al, 2007;Luo et al, 2012).…”
mentioning
confidence: 99%
“…Deactivation of CBB cycle enzymes is thought to prevent photorespiration of carbon in the absence of NADPH, which would waste ATP in the process. In fact, recent biochemical and proteomic studies have indicated that all 11 enzymes as well as several associated regulatory proteins of the CBB cycle may be redox regulated (Michelet et al, 2013).…”
Section: Redox Regulation Of Photosynthetic Enzyme Activitymentioning
confidence: 99%
“…In addition to energy dissipation, zeaxanthin plays a major role in ROS scavenging and detoxification (Dall'Osto et al, 2010). Additional ROS detoxification is mediated by glutathione peroxidases, peroxiredoxins and methionine sulfoxide reductases which are regenerated by thioredoxins (Michelet et al, 2013). …”
Section: -5)mentioning
confidence: 99%
See 1 more Smart Citation